STRATEGI PERPUSTAKAAN FAKULTAS ILMU SOSIAL DAN ILMU POLITIK (FISIP) UNIVERSITAS TANJUNGPURA DALAM MENGHADAPI VANDALISME - Maya Kurnia; Sahidi Sahidi (Universitas Tanjungpura, 2021)
AbstractActs of vandalism are often found in libraries but few libraries take the problem ofvandalism seriously. Acts of vandalism should be of particular concern to librarymanagers. This act of vandalism can have a huge impact on the library if notproperly addressed.This study discusses the Library Strategy of the Faculty of Socialand Political Sciences (Fisip) of Tanjungpura University in dealing with vandalism.The purpose of this study is to determine the factors that cause vandalism, strategiesto deal with vandalism and the policies taken to prevent and minimize vandalism.This study uses descriptive qualitative methods with data collection techniques,namely observation, interviews and documentation. The number of informants in thisstudy consisted of the head of the library, one library staff circulation section andthree users. The results of this study indicate that there are three factors that causevandalism. One of the strategies used by the Untan Fisip library in dealing withvandalism is to increase literature/collections. One of the policies taken to preventand minimize vandalism is to emphasize the layout of users when they are in thelibrary, to impose sanctions and to conduct security evaluations.Keywords: Library, Strategy, Vandalism